Science Fiction and Its Others. - Freedman, Carl (Science Fiction Studies, 2011)
The article reviews the books "Tech-Noir: The Fusion of Science Fiction and Film Noir" by Paul Meehan and "Limits of Horror: Technology, Bodies, Gothic" by Fred Botting.